Farmers’ preferences for east African highland cooking banana ’Matooke’ hybrids and local cultivars - Madalla, N.; Swennen, R.; Brown, A.; Carpentier, Sebastien C.; Bergh, I. van den; Crichton, R.J.; Marimo, Pricilla; Weltzien, Eva; Massawe, C.; Shimwela, M.; Mbongo, D.; Kindimba, Grace; et al. (Springer, 2023)
Background An understanding of farmers' preferences of new banana cultivars and their characteristics is critical for developing and selecting cultivars that meet consumer needs. Therefore, phenotypic selection in a genetically variable population remains an important aspect of plant breeding.